Phenomenology of Practice: A Valuable Way to Gain Pathic Knowledge in Medical Education - hakimeh sabeghi; leila afshar; shahram yazdani (Kerman University of Medical Sciences, 2022)
Phenomenology of practice is a useful method for deeply understanding human phenomena and is fundamentally practical. Its ultimate goal is to nurture thoughtfulness and tact in the practice of professions. Pathic knowledge is a type of non-cognitive knowledge which is obtained through phenomenology of practice and can provide a lens for teachers and students to reflect on their teaching and learning experiences through their relationships, their situations, and their acts. From Van Manen's point of view, what distinguishes practice from theory is not that practice exerts thought and concepts in the real world; rather, phenomenology of practice involves a different path of recognizing the world. It is very important in medical education due to the importance of communication and human interactions. In this letter, the author highlighted the importance of pathic knowledge in medical education as a part of professional knowledge.